2014
DOI: 10.18632/oncotarget.2579
|View full text |Cite
|
Sign up to set email alerts
|

Apoptin enhances the oncolytic properties of vaccinia virus and modifies mechanisms of tumor regression

Abstract: A recombinant vaccinia virus VVdGF-ApoS24/2 expressing apoptin selectively kills human cancer cells in vitro [Kochneva et al., 2013]. We compared the oncolytic activity of this recombinant with that of the parental strain L-IVP using a model of human A431 carcinoma xenografts in nude mice. Single intratumoral injections (2×107 PFU/mouse) of the viruses produced a dramatic decrease in tumor volumes, which was higher after injection of apoptin-producing virus. The tumor dried out after the injection of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
(53 reference statements)
0
28
0
1
Order By: Relevance
“…Our previous study [ 20 ] revealed high titers of the L-IVP strain in carcinoma A431 xenografts on days 2 and 4 after virus injection: 2.3 × 10 8 PFU/mL and 1.2 × 10 9 PFU/mL. The maximum viral concentration in the tumor was reached on day 8 post injection (2.6 × 10 9 PFU/mL).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Our previous study [ 20 ] revealed high titers of the L-IVP strain in carcinoma A431 xenografts on days 2 and 4 after virus injection: 2.3 × 10 8 PFU/mL and 1.2 × 10 9 PFU/mL. The maximum viral concentration in the tumor was reached on day 8 post injection (2.6 × 10 9 PFU/mL).…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, on day 55 the tumor volume in virus and saline injected mice differed by more than 6 times. These results led to the conclusion that active replication of the virus provides rapid destruction of the A431 carcinoma [ 20 ]. The Ehrlich solid carcinoma tumors injected with the L-IVP strain also decreased in size in comparison with saline-injected control mice ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations